MANAJEMEN STRATEGIS PENANGGULANGAN KEMISKINAN DI KOTA SURAKARTA - Wijayanti, Sumilir (JI@P, 2016)
Surakarta development policy has a priority in poverty reduction as theelaboration in Vision Mission Mayor and Deputy Mayor. The poverty rateSurakarta in 2010 amounted to 14.99%. Performance targets set in 2015 by10% with realization amounted to 10.97%. The performance targets set forpoverty reduction RPJMD Surakarta 2016-2021 City at 7.5%. This is theunderlying authors conducted a study analysis of strategic management forpoverty reduction in Surakarta covering (strategy formulation, strategyimplementation and assessment strategies) to describe poverty in Surakarta andwhat might be causing long-term targets are set is not reached.The study authors conducted a qualitative study with research sites in theSecretariat TKPKD Surakarta and Village (Gajahan, Serengan, Pajang, Sumberand Kepatihan Wetan). The poverty problem in Surakarta identified includeissues (health, education, employment, food security and basic welfareinfrastructure).The findings of the study of strategic management for poverty reduction inSurakarta, that : (1) in the formulation of the strategy, there are three factorsthat need attention : a. factor analysis of the external environment in order ofpriority on social issues, population and environment, b. factor internalanalysis in order to focus on CSRs participation in the allocation of resources,c. The annual target-setting by the functional division can be selected as thebasis for their next strategy. (2) in the implementation of the strategy there aretwo factors, that : a. integration of the functional division pattern is not clearlyvisible, is still partial and sectorial, for it needs to develop a correlation with afocus target poor people in the village with the highest poverty pockets, b.providing access to information and education to the poor, the development ofinnovation to be equipped with operational support, and the need to build anintegrated system as well as providing space for public participation. (3) in theassessment of the strategy, there are two factors that : a. need consistency thatthe target of achieving long-term has not translated into the realization of theannual target of a functional division implementing poverty reductionprograms, b. to be reviewed the appropriateness and feasibility beneficiaries ofpoverty alleviation programs associated with the administration of residence,and c. dalah potential competitive advantage and the vocational culture can bedeveloped as a solution to poverty reduction.Keywords : Strategy, Formulation, Implementation, Assessment Strategies andAchieving Performance